2013
DOI: 10.5812/hepatmon.13162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anesthetic Drugs in Liver Apoptosis

Abstract: ContextThe modern practice of anesthesia is highly dependent ona group of anesthetic drugs which many of them are metabolized in the liver.Evidence AcquisitionThe liver, of course, usually tolerates this burden. However, this is not always an unbroken rule. Anesthetic induced apoptosis has gained great concern during the last years; especially considering the neurologic system.ResultsHowever, we have evidence that there is some concern regarding their effects on the liver cells. Fortunately not all the anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 141 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…This is in contrast to previous anesthetics, where TFA is detectable in urine for up to 12 days after 75 minutes of anesthesia ( 41 - 43 ). However, sevoflurane has a low hepatotoxic potential as described in the current available literature ( 8 , 44 , 45 ). As apparently, sevoflurane is unlikely to cause severe postoperative hepatic injury and is an ideal anesthetic for patients with previous exposure to other halogenated anesthetics or hepatic disease ( 46 - 48 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This is in contrast to previous anesthetics, where TFA is detectable in urine for up to 12 days after 75 minutes of anesthesia ( 41 - 43 ). However, sevoflurane has a low hepatotoxic potential as described in the current available literature ( 8 , 44 , 45 ). As apparently, sevoflurane is unlikely to cause severe postoperative hepatic injury and is an ideal anesthetic for patients with previous exposure to other halogenated anesthetics or hepatic disease ( 46 - 48 ).…”
Section: Resultsmentioning
confidence: 91%
“…Within a few years of its introduction, cases of halothane-induced liver injuries were reported. In 1969, the National Institutes of Health (NIH) organized an epidemiological study on 250000 cases of halothane administration, which revealed an incidence of fatal hepatic necrosis of about 1 in 35000 individuals ( 6 - 8 ). Concerns about its hepatotoxicity eliminated the use of this anesthetic for adults in the United States and many other countries.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature, halothane and sevoflurane have been reported as volatiles with the most and least associated complications, respectively ( 13 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Anesthesia is a modern intervention that was first introduced in 1846 ( 13 - 16 ). Ether and chloroform were used as anesthetic agents before the 1950s, despite awareness of numerous side effects.…”
Section: Contextmentioning
confidence: 99%
“…Isoflurane undergoes minimal biotransformation; however, a wide spectrum of hepatotoxicity ranging from transaminitis to fulminant hepatic failure induced by isoflurane has been observed (5)(6)(7)(8). It has been demonstrated that the oxidative stress response, and hepatic necrosis and apoptosis, are involved in the liver injury mechanism (9,10); however, the exact mechanisms underlying this action have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%